Thực trạng quản lí hoạt động phòng chống dịch bệnh Covid-19 tại các trường tiểu học Quận 7, Thành phố Hồ Chí Minh - Lê , Thái Minh Long; Nguyễn , Văn Chiến (Tạp chí Giáo dục, 2021)
Preventing and providing treatment against the Covid-19 epidemic is currently a major issue of the entire society. Therefore, schools also have the responsibility of ensuring the prevention of the disease to ensure the safety of students. This paper explores the administrative management of preventative measures against Covid-19 epidemic at primary schools in District 7, Ho Chi Minh City. Results of our research has found out that primary schools in District 7, Ho Chi Minh City did pay attention to and performed their administrative functions frequently and effectively. Such results serve as the basis for proposing measures to improve the effectiveness of the procedure in the future.